TALAQQI RUKBAN AND IHTIKAR IN THE TRADITIONAL MARKET AT MAKASSAR IN PERSPECTIVE OF ISLAMIC ECONOMIC LAWS - Nurnaningsih Nawawi (Jurnal Ilmiah Al-Syir'ah, 2020)
This article discusses talaqqi rukban, a buying and selling tactic that seen as violating Islamic Economic Law. Where this practice is detrimental to sellers who sell their agricultural products because they are hindered by unscrupulous buyers who offer the prices of such farm products at prices far below the actual market price. This trading system, of course, is a fraud because the seller of agricultural products does not know the actual price and suffers from it. There are also sellers in the market monopolize certain goods in the market so that the costs of these goods rise dramatically. Sellers who carry out the monopoly get big profits while the people who become consumers are disadvantaged. This practice in Islam is called Ihtikar. This research uses descriptive qualitative research methods with a normative sociologies approach. In Islamic Economic Law, this practice strictly prohibited. It is a prohibited sale and purchase, but in Makassar, the practice of Talaqqi Rukban and Ihtikar still often occurs, whereas when viewed from the background of the Talaqqi Rukban and Ihtikar perpetrators are religious people. Of course, the practice is following Islamic Economic Law based on the Qur'an and Hadith. This research will propose a system, form, and analysis of some views of Jumhur scholars about the law, the terms of sale and purchase, which are: forbidden, obligatory, Sunnah, and makruh following Islamic economic law.